2021
DOI: 10.1128/jcm.00971-21
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of an Automated Plate Assessment System (APAS Independence) and Artificial Intelligence (AI) to Manual Plate Reading of Methicillin-Resistant and Methicillin-Susceptible Staphylococcus aureus CHROMagar Surveillance Cultures

Abstract: Background: The Automated Plate Assessment System (APAS Independence) [Clever Culture System, Bäch, Switzerland] is an automated imaging station linked with interpretive software that detects target colonies of interest on chromogenic media and sorts samples as negative or presumptive positive. We evaluated the accuracy of the APAS to triage methicillin-resistant Staphylococcus aureus (MRSA) and S. aureus ) cultures using chromogenic media compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Not requiring manual verification of the results is advantageous because it cuts down the time needed for patients to receive a final report. This key difference has resulted in the classification of the APAS Independence as a class II medical device in the United States, and it is the only such classified device ( 4 ). While our laboratory urine culture volumes only resulted in a savings of approximately 1 h of hands-on time, greater urine culture volumes likely would have resulted in more substantial time and labor savings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Not requiring manual verification of the results is advantageous because it cuts down the time needed for patients to receive a final report. This key difference has resulted in the classification of the APAS Independence as a class II medical device in the United States, and it is the only such classified device ( 4 ). While our laboratory urine culture volumes only resulted in a savings of approximately 1 h of hands-on time, greater urine culture volumes likely would have resulted in more substantial time and labor savings.…”
Section: Discussionmentioning
confidence: 99%
“…UTIs can be caused by a myriad of bacterial pathogens, and there is some subjectivity in the interpretation of urine culture results. Consequently, diagnoses can be subject to variation among the technicians analyzing culture results ( 4 ). The gold standard for processing a urine test involves planting a urine specimen onto culture medium and enumerating the potential pathogens to determine whether there is sufficient growth to be reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the years of training and professional desire to be 100% accurate 100% of the time, this is unfortunately not realistic. There is a fundamental risk with any manual interpretation of a culture plate that the interpretation is incorrect, especially when looking for single colonies amongst commensal flora ( Gammel et al, 2021 ). Non-consensus results between microbiologists have also been reported by Glasson et al (2016) who found that agreement between microbiologists for colony morphology is 97.5% when reading MacConkey agar but only 87.5% when reading blood agar.…”
mentioning
confidence: 99%
“…Currently, the PhenoMatrix™ (Copan Italia, Brescia, Italy) application provides an assessment of an agar plate in conjunction with expert rules where the user must accept the decision from the algorithm to proceed with reporting or further work, with published studies covering group B Streptococcus and Streptococcus pyogenes ( Van et al, 2019 ; Baker et al, 2020 ). The APAS ® Independence (Clever Culture Systems) is currently the only system with FDA clearance as a class II medical device which is diagnostic for a negative no growth result from urine samples ( Glasson et al, 2017 ), and for no significant growth when used in MRSA detection ( Gammel et al, 2021 ). In these cases, human intervention is only required for significant growths.…”
mentioning
confidence: 99%